2013
DOI: 10.1038/cdd.2013.94
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 contributes to TNFR1-mediated RIPK1 kinase-dependent apoptosis in conditions of cIAP1/2 depletion or TAK1 kinase inhibition

Abstract: Receptor-interacting protein kinase (RIPK) 1 and RIPK3 have emerged as essential kinases mediating a regulated form of necrosis, known as necroptosis, that can be induced by tumor necrosis factor (TNF) signaling. As a consequence, inhibiting RIPK1 kinase activity and repressing RIPK3 expression levels have become commonly used approaches to estimate the contribution of necroptosis to specific phenotypes. Here, we report that RIPK1 kinase activity and RIPK3 also contribute to TNFinduced apoptosis in conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
254
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 276 publications
(279 citation statements)
references
References 49 publications
14
254
0
1
Order By: Relevance
“…We recently showed that the RIP1 kinase inhibitor necrostatin-1 (Nec-1) prevented SM/TNFα-induced caspase activation. 19 Similarly, we observed that Tweak/TNFα-or agonist LTβR /TNFα-induced caspase activation was equally inhibited in the presence of Nec-1 or Z-Val-Ala-DL-Aspfluoromethylketone (z-VAD-FMK) (Figures 2c and d). We also found that Tweak/TNFα-or agonist LTβR/TNFα-induced RIP1/caspase-8 assembly was fully abrogated in the presence of Nec-1 (Figures 2e and f).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…We recently showed that the RIP1 kinase inhibitor necrostatin-1 (Nec-1) prevented SM/TNFα-induced caspase activation. 19 Similarly, we observed that Tweak/TNFα-or agonist LTβR /TNFα-induced caspase activation was equally inhibited in the presence of Nec-1 or Z-Val-Ala-DL-Aspfluoromethylketone (z-VAD-FMK) (Figures 2c and d). We also found that Tweak/TNFα-or agonist LTβR/TNFα-induced RIP1/caspase-8 assembly was fully abrogated in the presence of Nec-1 (Figures 2e and f).…”
Section: Resultsmentioning
confidence: 57%
“…These results are consistent with previous studies demonstrating a role for Nec-1 in the prevention of SM/TNFα-induced RIP1/caspase-8 assembly and apoptosis. 19,41 We further found that the DEVDase activity induced by Tweak/TNFα co-stimulation was strongly reduced in Bax/Bak − / − double KO MEFs when compared with Bax/Bak +/+ counterparts MEFs (Supplementary Figure S2e). Likewise, treatment of Bax/ Bak − / − MEFs with Tweak and TNFα resulted in a slight alteration of caspase-8 processing but in a complete inhibition of caspase-3 cleavage when compared with Bax/ Bak +/+ counterparts control MEFs, indicating that caspase-8 processing precedes the Bax/Bak-mediated activation of the executioner caspases (Supplementary Figure S2f).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…49 In line with this, combined inhibition of caspase and RIPK3 rescues TNFa-induced cell death in Tak1-deficient cells. 58,[77][78][79] These results suggest that, although the default pathway of cell death in Tak1-deficient cells is apoptosis, Tak1 deficiency engages an alternative RIPK1-RIPK3 necroptosis pathway if the default pathway is blocked. Interestingly, even though RIPK1 was believed to be an essential mediator of RIPK3 activation, necroptosis can still be engaged with Ripk1 deletion.…”
Section: Tak1 As a Necroptosis Inducermentioning
confidence: 91%
“…To identify genes positively involved in the ER stress-induced cell death pathway, genes providing at least 30% protection upon repression were selected and defined as 'hits' (Figures 1b and c and Supplementary Tables 1 and 2). This led us to the identification of 22 genes (Figure 1c), out of which 7 were validated by kinetic cell death analysis measuring nuclear SytoxGreen fluorescence in death cells (Fluostar Omega fluorescence plate reader, BMG Labtech, Ortenberg, Germany), as previously described 19 (Figures 1d-j and Supplementary Figure 1). Of note, two of these seven genes, Pmaip1 (Noxa) and Bad, are reported mediators of ER stress-induced death, 20,21 confirming the validity of our screen.…”
Section: Resultsmentioning
confidence: 82%